Experimental investigation of increasing heat transfers inside a double pipe heat exchanger by using Al2O3 nanofluid - Mohamed, Hozaifa Adel; Negeed, El-Sayed Rajab; Alhazmy, Majed Mala (Journal of engineering sciences and information technology, 2022)
The aim of the present study is to investigation of increasing of the heat transfer coefficient inside the double tube. This is done by mixing water with aluminum oxide nanoparticles (Al2O3), the study was carried out experimentally. In this study, the effects of nanofluids at different volume concentrations from 0.05% to 0.4%, different mass flow rates of the nanofluids inside the tube, and different mass flow rates of the water flow through the annulus were tested. Experiments done with different nanoparticles and without nanoparticles under the same operating conditions. The experiment was designed, and built in the laboratory according to the international specifications and standards of the tubular exchanger manufacturers association (TEMA). By collecting and analyzing the results of the experiments, it was found that the nanoparticles have a significant improvement in the heat transfer coefficient inside the double tube. The heat transfer coefficient inside the tube increases with the increase the Reynolds number of the tube flow. The maximum value of the Nusselt number is when the volume concentration of Al2O3 nanoparticles is 0.1%.
Keywords: Double pipe heat exchanger; enhance the heat transfer rate; heat transfer double pipe with Al2O3 nanofluid